2016
DOI: 10.1039/c6ra03466g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and stable perovskite solar cells based on functional graphene-modified P3HT hole-transporting layer

Abstract: Organic–inorganic perovskite solar cells have recently emerged at the forefront of photovoltaics research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 34 publications
2
27
3
Order By: Relevance
“…This problem can be partially addressed by blending P3HT with graphene. Recently, Ye et al reported an imidazole‐functional‐graphene (I‐F‐Graphene):P3HT composite as HTL for a mesoscopic HPSC of FTO/cp‐TiO 2 /mp‐TiO 2 /MAPbI 3 /I‐F‐Graphene:P3HT/Ag . I‐F‐Graphene was dispersed into P3HT to improve the hole mobility, conductivity and hydrophobicity of this composite HTL.…”
Section: D Materials For Halide Perovskite Solar Cellsmentioning
confidence: 99%
“…This problem can be partially addressed by blending P3HT with graphene. Recently, Ye et al reported an imidazole‐functional‐graphene (I‐F‐Graphene):P3HT composite as HTL for a mesoscopic HPSC of FTO/cp‐TiO 2 /mp‐TiO 2 /MAPbI 3 /I‐F‐Graphene:P3HT/Ag . I‐F‐Graphene was dispersed into P3HT to improve the hole mobility, conductivity and hydrophobicity of this composite HTL.…”
Section: D Materials For Halide Perovskite Solar Cellsmentioning
confidence: 99%
“…Researches have been carried out employing P3HT as dopant‐free HTM for PSCs during the years 2015 and 2016, and PCEs about 6.17, 7.5, 8.3, and 11.8%, have been reported. Significant power conversion efficiency of up to 13.82% has been reported in 2016 by Ye et al for PSC devices using P3HT modified with F‐graphene as HTM . In 2017, however, in a research by Colorado, two different conjugated polymers, P3HT and PTB7:Th ( 8 ) were employed as dopant‐free HTMs in PSCs .…”
Section: Dopant‐free Hole Transporting Materials For Pscsmentioning
confidence: 99%
“…[55,56] GRMs are very versatile, offering ap ossibility to control the bandgap andb and alignment through chemical functionalization and edge modification. [68][69][70][71][72][73] In this work, we report ad etailed study focused on the stability of PSCs, with GRMs used in different components of the PSC. Moreover,t he use of liquid-phasee xfoliated (LPE) graphene flakes, [63] as well as graphene produced by bottom-up approaches, [64][65][66][67] can boost the charge-transport dynamics at the photo electrode (PE).…”
Section: Introductionmentioning
confidence: 99%
“…Finally,t he use of GRMs in PSCs has also been demonstratedt ob eb eneficial to increase devices lifetimeunder different stress conditions. [68][69][70][71][72][73] In this work, we report ad etailed study focused on the stability of PSCs, with GRMs used in different components of the PSC. This allowsu st oa ssess the influenceo fG RMs on the stability of PSCs.…”
Section: Introductionmentioning
confidence: 99%